A Review on Time-Driven Activity-Based Costing System in Various Sectors - Sri Nur Areena, Mohd Zaini; Abu, Mohd Yazid (Penerbit UMP, 2019)
Time-Driven Activity-Based Costing is a type of method which can describe as a costing model that consider a time which known as inducer time. This method is providing the cost of activities with base that consume of time per activities. In this study, published works was based on literature studies from 56 journals from period 2011-2018 which including in area of healthcare, industrial and library. The study reported only 10 papers out of previous 56 papers that focus for more efficient as their main advantage from using Time-Driven Activity-Based Costing’s four methods which are process map, capacity cost rate (CCR), time equation and forecasting. However, there is no paper show the methodology uses of Time-Driven Activity-Based Costing in palm oil plantation. The aim of this study is to explore the research gap of Time-Driven Activity-Based Costing in the journals that can be as guideline in applying Time-Driven Activity-Based Costing system in palm oil plantation. In this study, Time-Driven Activity-Based Costing is a new system able to apply in various environments in order to get better process in each workstation and also the time will be more accurate in each activity or sub-activities of a product. This costing method can also increase organizations' profits because the unused product capacity is counted in this method. The advantage of TDABC is that it provides an accurate cost accounting starting point for providers. As resources become more limited in the future, providers will need to understand their real costs in the provision of specific services.